Teaching and learning about genocide and crimes against humanity : fundamental issues and pedagogical approaches - Totten, Samuel (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"Teaching and Learning About Genocide and Crimes Against Humanity: Fundamental Issues and Pedagogical Approaches by Samuel Totten, a renowned scholar of genocide studies and Professor Emeritus, College of Education and Health Professions, University of Arkansas, Fayetteville, is a culmination of 30 years in the field of genocide studies and education. In writing this book, Totten reports that he "crafted this book along the lines of what he wished had been available to him when he first began teaching about genocide back in the mid-1980s. That is, a book that combines the best of genocide theory, the realities of the genocidal process, and how to teach about such complex and often torturously terrible and difficult issues and facts in a theoretically, historically and pedagogically sound manner. As the last book he will ever write on education and educating about genocide he perceives the book as his gift to those educators have the heart and grit to tackle such an important issue in their classrooms"-- Provided by publisher.
Keywords: Genocide -- Study and teaching.; Crimes against humanity -- Study and teaching.; Education -- Teaching -- Subjects -- General.; Teaching of a specific subject.; elektronické knihy; electronic books